Baryon acoustic oscillation, Hubble parameter, and angular size measurement constraints on the Hubble constant, dark energy dynamics, and spatial curvature. Issue 3 (17th July 2019) - Ryan, Joseph; Chen, Yun; Ratra, Bharat
ABSTRACT: In this paper, we use all available baryon acoustic oscillation, Hubble parameter, and quasar angular size data to constrain six dark energy cosmological models, both spatially flat and non-flat. Depending on the model and data combination considered, these data mildly favour closed spatial hypersurfaces (by as much as 1.7σ) and dark energy dynamics (up to a little over 2σ) over a cosmological constant Λ. The data also favour, at 1.8σ to 3.4σ, depending on the model and data combination, a lower Hubble constant than what is measured from the local expansion rate.